Coloring Picture Play Therapy for Preschool-aged Children to Improve Fine Motoric Skills at Madrasah Al-Istiqomah Ciamis - Roslianti, Elis; Firmansyah, Andan; Setiawan, Henri; Suhanda, Suhanda; Fitriani, Ade; Hamdani, Dadi (ABDIMAS: Jurnal Pengabdian Masyarakat, 2023)
Children are individuals who still have a dependence on adults and the surrounding environment. Pre-schoolers are children aged 3-6 years, at this time children's imagination and creativity begin to develop, and in fine motor development children are able to hold writing tools correctly and learn to draw and color. Coloring is the activity of giving colour to the desired field or object. Colouring is an activity that can hone children's creativity and is one of the arts that children like and is easy to learn and can stimulate the performance of the right brain which is very important for children's intelligence. The purpose of holding Picture Colouring Play Therapy for Pre-schoolers is to improve fine motor skills in pre-schoolers (3-6 years). The method used in this activity is the play therapy method where this activity begins with exploring the target, namely Madrasah Al-Istiqomah. The number of children involved in this activity was 15 children who also participated in the Picture Colouring Play Therapy activity, all of whom were students of Madrasah Al-Istiqomah. The results of this play therapy activity showed that children were very enthusiastic in carrying out play therapy activities, and colouring pictures, several things that became a benchmark for the success of therapy were the improvement of children's fine motor skills seen from the accuracy, neatness, and creativity of children. The conclusion of this activity is in accordance with the results of the evaluation of Picture Colouring Play Therapy for Pre-schoolers which has been successfully carried out with satisfactory results criteria where children are enthusiastic in carrying out these activities and this activity can improve the fine motor skills of children, especially preschool age (3-6). year).